PERAN RELATIONSHIP MANAGER DALAM MEMBINA HUBUNGAN BAIK DENGAN CUSTOMER , STUDI PADA CIMB NIAGA PONDOK INDAH - Dewi Retno Budiastuti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
The job or position of a manager in a company, one of that is Relationship Manager. This position is often understood as one of the sales positions in the company, but this position also has various job descriptions other than as a salesperson in the company. Relationship Manager or relationship manager is a person who has the duty and responsibility to build and maintain good relations between the company and the parties seen in it, such as partners and clients of the company. Research methods this research uses qualitative research methods, research conducted at Bank CIMB Niaga branch Pondok Indahactivities carried out RM CIMB Niaga in establishing good relations with customers include updating customer data, daily meetings through conference calls, meetings with bank partners, recognizing customers personally, Receiving suggestions and complaints from customers, giving gifts to customers, holding events and inviting customers to events the efforts made by bank CIMB Niaga and RM have been quite helpful for RM in establishing good communication with customers. With good communication it will create a harmonious relationship between the bank and the customer. The good and harmonious relationship created will help RM's work process in the future, namely in introducing and selling bank products.